Islamic Review of Paid Waqf Mosque Toilets - Ibnu Budiyanto, Mar’ie Faiq; Hasan, Nur; Muhibban (ALFATWA jurnal tentang hukum dan syariat, 2025)
This study aims to analyze the Islamic views on the paid toilet policy of waqf mosques in the Depok area and to explore the Islamic views on the policy and its implications for the community. This problem arises along with the increasing number of waqf mosques that implement a paid system for toilet use, which raises debates about its validity and social impact. The method used in this research is a qualitative approach with in-depth interviews with mosque managers, scholars, and mosque worshipers as well as a literature study on Islamic law related to waqf and public facilities.The results show that the majority of scholars consider that mosque toilets should be a free facility for Muslims, because mosques are places of worship that are endowed for public use. However, there are some views that allow administrative costs for the maintenance of these facilities, while still taking into account the benefits of the people. The conclusion of this study is that the policy of paid waqf mosque toilets needs to be reconsidered in terms of Islamic law and social justice, taking into account the welfare of the people and the sustainability of mosque maintenance. research results.